HIGH-PRESSURE PARTIAL MELTING OF MAFIC LITHOLOGIES IN THE MANTLE - Kogiso T.; Hirschmann M.M.; Pertermann M. (My University, 2004)
We review experimental phase equilibria associated with partial melting of mafic lithologies (pyroxenites) at high pressures to reveal systematic relationships between bulk compositions of pyroxenite and their melting relations. An important aspect of pyroxenite phase equilibria is the existence of the garnet–pyroxene thermal divide, defined by the enstatite–Ca-Tschermaks pyroxene–diopside plane in CaO–MgO–Al2O3–SiO2 projections. This divide appears at pressures above ?2?GPa in the natural system where garnet and pyroxenes are the principal residual phases in pyroxenites. Bulk compositions that reside on either side of the divide have distinct phase assemblages from subsolidus to liquidus and produce distinct types of partial melt ranging from strongly nepheline-normative to quartz-normative compositions. Solidus and liquidus locations are little affected by the location of natural pyroxenite compositions relative to the thermal divide and are instead controlled chiefly by bulk alkali contents and Mg-numbers. Changes in phase volumes of residual minerals also influence partial melt compositions. If olivine is absent during partial melting, expansion of the phase volume of garnet relative to clinopyroxene with increasing pressure produces liquids with high Ca/Al and low MgO compared with garnet peridotite-derived partial melts.